Análise do processo de verticalização no espaço urbano de Cascavel/PR entre os anos de 1990 e 2008 - Santos, Edson Marcos dos (2011)
Inside the cities we find one of the forms occupation of the ground urban wich is the verticalization. It can`t be affirmed when the verticalization occurs the ground urban is ending. The producers of this form of occupation of the ground urban if appropriate of the same as form of investments and also for real estate speculation and not for trying to decide the problem of the lack of constructions it is for housing or the commerce. This form of occupation of the ground urban has modified the landscape of some cities beyond fortifying the process of urban segregation. Being the city the result of the social relations, the verticalization is a good example of these relations. To look for to understand as and because the verticalization occurs in some cities if makes necessary as form to understand which are the agents who participate and produce the same one. Some cities in the last times had passed for a economic growth and had started to pass for the verticalization process. This work makes an analysis of the process of allied verticalization to the economic growth of the Cascavel-PR city in the period of 1990 the 2008 searching to understand as this occurred.